THE EFFECTIVENESS OF HYPNOTEACHING TO IMPROVE MOTIVATION AND SELF-EFFICACY OF STUDENTS OF MUHAMMADIYAH ELEMENTARY SCHOOL SAMARINDA - Ummu Khairin Nisa; Zurqoni Zurqoni; Shafa Shafa (Jurnal Konseling Pendidikan Islam, 2026)
Low learning motivation and self-efficacy among students, resulting from the dominance of conventional teaching methods, represent a serious challenge in Islamic elementary education. This study aims to examine the effectiveness of the hypnoteaching method in improving the learning motivation and self-efficacy of fourth-grade students at SD Muhammadiyah Samarinda. The research employed a quantitative approach with a quasi-experimental non-equivalent control group design, involving 106 students from SD Muhammadiyah 2 and SD Muhammadiyah 5 Samarinda selected through cluster random sampling. Data were collected through questionnaires, observations, and documentation, then analyzed using independent sample t-tests, N-Gain Score, and effect size (Cohen's d). The results demonstrate that hypnoteaching effectively enhances learning motivation with a medium effect size (Cohen's d = 0.576) and substantially improves self-efficacy with a large effect size (Cohen's d = 0.914). However, the N-Gain Score values for both variables remain low (16.55% and 14.15%), indicating the need for extended intervention duration and intensity. These findings imply that hypnoteaching is worthy of broad implementation as a psychologically responsive innovative learning strategy within Islamic elementary education contexts.